Concise synthesis of the A/BCD-ring fragment of gambieric acid A - Fuwa, Haruhiko; Fukazawa, Ryo; Sasaki, Makoto (Frontiers in Chemistry, 2015)
Gambieric acid A (GAA) and its congeners belong to the family of marine polycyclic ether natural products. Their highly complex molecular architecture and unique biological activities have been of intense interest within the synthetic community. We have previously reported the first total synthesis, stereochemical reassignment, and preliminary structure–activity relationships of GAA. Here we disclose a concise synthesis of the A/BCD-ring fragment of GAA. The synthesis started from our previously reported synthetic intermediate that represents the A/B-ring. The C-ring was synthesized via an oxiranyl anion coupling and a 6-endo cyclization, and the D-ring was forged by means of an oxidative lactonization and subsequent palladium-catalyzed functionalization of the lactone ring. In this manner, the number of linear synthetic steps required for the construction of the C- and D-rings was reduced from 22 to 11.